PROSPEK PENGEMBANGAN USAHA DODOL PEPAYA (Carica papaya L.) PADA HOME INDUSTRI “DUA SAUDARA” DESA TEBAT MONOK KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Pariang Simanjuntak; Herri Fariadi; Rika Dwi Yuli H (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Basically fruit plants can be increased by the value added process into different kinds of food. One of the products processed in the District Kepahiang made from raw papaya (Carica papaya L.) is a papaya dodol. The development of industrial-scale processing dodol small business has good prospects given the potential market is very supportive. Furthermore the process of making fruit dodol basically not too difficult and it has economic value is quite tempting. Hence arose the idea to cultivate papaya that has selling value and extend shelf life. The purpose of this study was to identify the development prospects papaya dodol processing home industry